2010
DOI: 10.1097/cco.0b013e32833aafef
|View full text |Cite
|
Sign up to set email alerts
|

Update on gemcitabine and docetaxel combination therapy for primary and metastatic sarcomas

Abstract: Fixed-dose-rate gemcitabine and docetaxel is a reasonable treatment option for patients with advanced soft-tissue sarcoma. The regimen is a good choice as first-line or second-line therapy for advanced uterine leiomyosarcoma. The role of adjuvant gemcitabine-docetaxel in completely resected, uterine-limited, high-grade leiomyosarcoma is under investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…A later study of 122 patients, 38 (31%) of whom had LMS, showed a response rate of 11% with gemcitabine alone versus 27% in LMS treated with the combination of gemcitabine-docetaxel. The study showed that, for metastatic STS including LMS, OS and PFS were superior with gemcitabine-docetaxel versus gemcitabine alone (17.9 vs 11.5 and 6.2 vs 3.0 months, respectively) [19]. This supported previous trials in advanced STS showing promise for this doublet [18•, 20, 21].…”
Section: Conventional Systemic Therapies For Lmsmentioning
confidence: 69%
See 1 more Smart Citation
“…A later study of 122 patients, 38 (31%) of whom had LMS, showed a response rate of 11% with gemcitabine alone versus 27% in LMS treated with the combination of gemcitabine-docetaxel. The study showed that, for metastatic STS including LMS, OS and PFS were superior with gemcitabine-docetaxel versus gemcitabine alone (17.9 vs 11.5 and 6.2 vs 3.0 months, respectively) [19]. This supported previous trials in advanced STS showing promise for this doublet [18•, 20, 21].…”
Section: Conventional Systemic Therapies For Lmsmentioning
confidence: 69%
“…Many studies have looked at karyotyping for LMS with little consistency, in keeping with the expected heterogeneity and complexity [46]. The chromosomal changes described in LMS include imbalances or aberrations in the form of gains (chromosomes 1, 5, 6, 8, 15, 16, 17, 19, 20, 22, X), losses (chromosomes 1p, 2, 3, 4, 6q, 8, 9, 10p, 11p, 12q, 11q, 13, 16, 17p, 18, 19, 22q), and amplifications (chromosomes 1,5,8,12,13,17,19,20). Some gains and losses of chromosomal material are more frequently observed and tend to correlate with poor outcome, large tumor size, and metastatic disseminationeg, loss of 1p12-pter, 2p, 13q14-q21 (targeting the Rb pathway), 10q (targeting PTEN), and 16q; gains of 17p, 8q, and 5p14 pter [42].…”
Section: Novel Therapeutic Strategiesmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first to evaluate the efficacy and tolerability of G/P in patients with STS. The combination of taxanes and gemcitabine is increasingly utilized in STS, as well as in bone sarcoma (7)(8)(9)15). Early-phase II studies evaluating fixed-dose rate infusion of gemcitabine 900 mg/m 2 administered over 90 min (days 1 and 8) in combination with docetaxel 100 mg/m 2 (day 8) every 21 days, achieved objective response rates of 17-36%, with a median time-to-progression of 5.6-6.2 months (4,7).…”
Section: Discussionmentioning
confidence: 99%
“…While single-agent gemcitabine exhibited only modest activity, the overall response rates in phase II trials combining gemcitabine with docetaxel were in the range of 16-53% in this patient group (3-6). A higher efficacy with superior progression-free survival (PFS) and overall survival (OS) was also demonstrated with this combination in several comparative trials (3,7,8). Therefore, it became common practice in several sarcoma centers to initiate combination treatment, hypothesizing synergy between gemcitabine and docetaxel.…”
mentioning
confidence: 99%
“…En l'absence de toxicité cumulative (notamment cardiaque), le doublet de gemcitabine et docétaxel peut permettre un traitement prolongé [7] comme nous l'avons vérifié chez plusieurs de nos patients. Cette action apparaît dans beaucoup de sous-types histologiques plus cytostatique que cytotoxique, à l'instar des nouvelles thérapeutiques ciblées, inhibiteurs de tyrosine-kinase antiangiogéniques [18] ou inhibiteurs de m-TOR [3] dont l'effet antitumoral semble dans l'état actuel des études du même ordre.…”
Section: Réponse Au Traitement Et Survieunclassified